Assessing aesthetics preferences of Malay wood carved panels - Othman, Jamilah; Abdul Majid, Noor Hanita (Science International (Lahore), 2017)
Malay wood carvings are seen as man’s spontaneous reaction towards his environment when the availability of local material was used to achieve aesthetics value with functional natural ventilation. Thus, a study of wood carvings of the Malay vernacular houses should have equal concern for both issues. This paper assessed the public’s aesthetics preferences of twenty wood carved panels. The result of the survey shows that the panels with geometrical, calligraphy and floral motifs received the highest aesthetics preferences. Interestingly, the incisions of panels with more voids were highly preferred for. Similarly, panels with more voids have influenced the function of the natural ventilation better. In addition, the study also suggests that the elements of nature depicted on the panels have contributed higher aesthetics preferences of the public.